In Vitro Analyses Reveal the Effect of Synthetic Cytokinin Forchlorfenuron (FCF) on a Septin-Like Protein of Taeniid Cysticerci - Diana G. Rios-Valencia; Edgar O. López-Villegas; Dylan Diaz Chiguer; Adrian Marquez Navarro; Ruben D. Díaz-Martín; Benjamin Nogueda-Torres; Javier R. Ambrosio (Journal of Parasitology Research)
Cytokinin forchlorfenuron (FCF), a synthetic cytokinin, has been used specifically for the characterization of septins. In spite of genomic evidence of their existence, nothing is known about septin filaments in taeniid cestodes. The aim of this work was to determine the presence of a septin-like protein in cysticerci of Taenia crassiceps and Taenia solium using the deduced amino acid sequence of T. solium septin 4 (SEPT4_Tsm), to design and synthesize a derived immunogenic peptide (residues 88 to 103), to prepare a specific rabbit polyclonal antibody, and to examine the effects of FCF at different concentrations and exposure times on an in vitro culture of T. crassiceps cysticerci. In vitro, FCF altered the morphology and motility of T. crassiceps cysticerci, and its effects were reversible under specific concentrations. In addition, we observed by ultrastructural observation that FCF alters the cellular subunit of the protonephridial system of cestodes, where disruption of the axoneme pattern of flame cells was observed. The rabbit polyclonal antibody prepared against the synthetic peptide recognized a major band of 41 kDa in both parasites. Our results establish the importance of SEPT4_Tsm in the dynamics and survival of taeniid cysticerci, as well as their susceptibility to FCF. This is also the first report that a septin is present in the cytoskeleton of taeniids.